2018
DOI: 10.1038/ajg.2017.464
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Magnetic Resonance Enterography For Small Bowel Endoscopic Healing in Patients With Crohn's Disease

Abstract: SB inflammation was associated with a poor prognosis in patients with clinical-serological remission. MRE is a valid and reliable examination for SB inflammatory activity both for cross-sectional evaluations and prognostic prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 28 publications
3
76
0
Order By: Relevance
“…The increasing use of MRE in CD has introduced new challenges, including how to define remission and how to interpret discrepancies between endoscopic healing and persistence of transmural abnormalities in MRE assessments. While mucosal healing as assessed by ileocolonoscopy has been studied in depth, few studies have evaluated the characteristics of transmural healing assessed by means of MRE . Of note, residual mural abnormalities, such as wall thickening, or extramural lesions, like creeping fat, can persist in intestinal segments with endoscopic remission .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The increasing use of MRE in CD has introduced new challenges, including how to define remission and how to interpret discrepancies between endoscopic healing and persistence of transmural abnormalities in MRE assessments. While mucosal healing as assessed by ileocolonoscopy has been studied in depth, few studies have evaluated the characteristics of transmural healing assessed by means of MRE . Of note, residual mural abnormalities, such as wall thickening, or extramural lesions, like creeping fat, can persist in intestinal segments with endoscopic remission .…”
Section: Introductionmentioning
confidence: 99%
“…Of note, residual mural abnormalities, such as wall thickening, or extramural lesions, like creeping fat, can persist in intestinal segments with endoscopic remission . From the clinical point of view, it is crucial to determine whether these lesions represent established persistent damage (likely irreversible) or an inflammatory component that can heal with appropriate anti‐inflammatory therapy …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies have been reported retrospectively, and routine BAE's feasibility and diagnostic utility in clinical practice for CD have yet to be established [37,38]. However, several studies on BAE's utility for evaluating SB CD, and endoscopic treatment for strictures, have been reported in a prospective series from Japan [39][40][41][42].…”
Section: Balloon-assisted Endoscopymentioning
confidence: 99%